Development and reporting of a specialised antenatal music therapy intervention using the MRC framework and TIDieR checklist - Cheung, Pui Sze; Tighe, Sylvia Murphy; Mohamad, Mas Mahady; McCaffrey, Triona (Frontiers in Psychiatry, 2026)
IntroductionPerinatal mental health can significantly impact parental and infant wellbeing. Music interventions have shown promise in improving perinatal wellbeing during pregnancy. However, research in this area remains scarce, and very few structured music therapy programmes have been developed and reported in sufficient detail to enable replication and implementation in clinical settings. This article aims to describe the development process of a novel Specialised Antenatal Music Therapy (SAMT) intervention and provide a detailed report of this using the Template for Intervention Description and Replication (TIDieR) 12-point checklist.MethodsGuided by the Medical Research Council (MRC) framework for developing complex interventions, SAMT was developed through a systematic, evidence-based, theory-driven, and stakeholder-informed process. This included: (1) assembling a multidisciplinary expert team, (2) reviewing existing research evidence and antenatal music therapy protocols, (3) understanding the context and engaging stakeholders through research and co-creation, (4) drawing on existing theories and techniques to facilitate treatment outcomes, and (5) evaluating the feasibility and efficacy through a proof-of-concept study.ResultsThis systematic approach resulted in the development of SAMT - a novel music therapy programme for pregnant women attending a Specialist Perinatal Mental Health Service (SPMHS) in Ireland. SAMT consists of six weekly individual music therapy sessions, each lasting 45–60 minutes, delivered either online or in-person at the SPMHS outpatient clinic in a central location. Key components include music-assisted relaxation, identifying a bonding song, musical bonding, song discussion, songwriting, creating pregnancy/birth playlists, and creative music making. Early feasibility testing indicated that the intervention was acceptable and well received by participants.Discussion/conclusionUsing the TIDieR checklist to report complex interventions provides a structured, systematic way of conveying necessary detail. This method enables music therapists, clinicians, and researchers to understand the SAMT’s underlying rationale, theoretical foundation, delivery methods, and implementation considerations, facilitating replication, refinement, and integration into perinatal mental health services and research.